Middelkerke. Ruines. L'Eglise - The Church, GP051162 (2) - Auteur inconnu (Wikimedia Commons, 1920)
Carte postale ancienne issue de Wikimedia Commons. Titre: Middelkerke. Ruines. L'Eglise - The Church, GP051162 (2). Title Middelkerke. Ruines. L'Eglise - The Church Date 1920 Publisher Bruxelles: Marcovici Uniform title Middelkerke. Gebouwen. Kerken en kapellen. Sint-Willibrorduskerk Series Belgique. Province de Flandre occidentale. Cartes postales Belgium. Province of West-Flanders. Postcards België. Provincie West-Vlaanderen. Prentkaarten Genre Post cards Extent 1 kaart / postcard Graphic Brown Language French Additional info General note: Titelgegevens ontleend aan prentkaart Source Library Catalog Source ID lbsn9992504214901471
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale